DETERMINATION OF SUSPECTS IN CORRUPTION CRIMES BY POLICE INVESTIGATORS FROM A DUE PROCESS OF LAW PERSPECTIVE - Basar Achmad S Purba; Andi Maysarah; Dian Hardian Silalahi (NOMOI Law Review, 2026)
The extensive authority of Police investigators in determining suspects of corruption crimes often intersects with issues of arbitrariness and fundamental human rights protection. This study aims to analyze the reconstruction of suspect determination procedures based on Law Number 20 of 2025 and its juridical implications. As a theoretical and practical reference for legal practitioners, this research underscores the urgency of procedural compliance to ensure legal certainty. Employing normative legal research with statute and conceptual approaches , the discussion highlights a paradigm shift from broad discretion to mandatory scientific evidence, specifically requiring definitive state loss audits and "Special Case Exposure" involving external experts. The analysis confirms that the validity of suspect determination strictly depends on these limitative boundaries. The conclusion asserts that any violation constitutes an excess of power, rendering the suspect status null and void and the evidence invalid (fruit of the poisonous tree). Consequently, this research suggests that law enforcement must strictly adhere to these procedural safeguards to uphold the supremacy of due process in corruption eradication.